Ensuring value for money in health care the role of health technology assessment in the European Union - Sorenson, Corinna; Drummond, M. F.; Kanavos, Panos (Euro Nonserial Publication, 2008)
This book provides a detailed review of the role of health technology assessment (HTA) in the European Union. It examines both method and process in the prioritization and financing of modern health care and presents extensive case studies from Sweden, the Netherlands, Finland, France, Germany and the United Kingdom. The book examines a number of issues, with particular emphasis on the responsibility and membership of HTA bodies assessment procedures and methods, the application of HTA evidence to decision-making, and the dissemination and implementation of findings. It aims to highlight ways
Keywords: Medical technology : European Union countries : Evaluation; Medical technology : European Union countries : Finance